Eaze : marijuana delivered - Paschen, Jeannette, (SAGE Knowledge. Cases., 2019)
In 2014, entrepreneur Keith McCarty founded Eaze--a company connecting marijuana dispensaries and users via an online platform--out of his San Francisco apartment. Three years later, and after several rounds of venture capital funding, the company was rapidly growing. Originally, Eaze was designed to connect medical marijuana patients with products from local dispensaries. However, the legalization of marijuana beyond medical purposes in California opened the door to a large and growing customer base that Eaze now serves. With high market growth and an ever-changing regulatory landscape, the young company is faced with many challenges related to delivering excellent service to multiple customer bases. In addition, over time, customer ratings of the service have declined. Students are asked to consider what Eaze's business model is and to assess whether its service delivery meets the expectations of various customer segments.